The Role of GSK-3 in Cancer Immunotherapy: GSK-3 Inhibitors as a New Frontier in Cancer Treatment - Augello, Giuseppa (Cells, 2020)
The serine/threonine kinase glycogen synthase kinase-3 (GSK-3) was initially identified because of its key role in the regulation of glycogen synthesis. However, it is now well-established that GSK-3 performs critical functions in many cellular processes, such as apoptosis, tumor growth, cell invasion, and metastasis. Aberrant GSK-3 activity has been associated with many human diseases, including cancer, highlighting its potential therapeutic relevance as a target for anticancer therapy. Recently, newly emerging data have demonstrated the pivotal role of GSK-3 in the anticancer immune response. In the last few years, many GSK-3 inhibitors have been developed, and some are currently being tested in clinical trials. This review will discuss preclinical and initial clinical results with GSK-3β inhibitors, highlighting the potential importance of this target in cancer immunotherapy. As described in this review, GSK-3 inhibitors have been shown to have antitumor activity in a wide range of human cancer cells, and they may also contribute to promoting a more efficacious immune response against tumor target cells, thus showing a double therapeutic advantage.